Implementation of the Futsal Learning Model as a Means of Developing Social Skills in Students at SMA Negeri 3 Sukoharjo - Fadli, Rofi Azka Al; Fatoni, Muhad; Sistiasih, Vera Septi; Subekti, Nur (Fair Play, 2025)
The purpose of this study is to explore the implementation of the futsal learning model as a means of developing students' social skills at SMA Negeri 3 Sukoharjo. The research method used is quasi-experimental research because this study aims to determine students' social development through futsal learning. The research design used in this study is a one-group pre-test-post-test design. In the one-group pre-test-post-test design, only one group is the target of the experiment, with no control group. The research sample was selected using purposive sampling. The results of the data analysis show a significant increase between the pre-test and post-test scores, with a ratio of 131.10:149.71, reflecting an increase of approximately 14.2%. Based on the research results, it can be concluded that the futsal learning model is effective in developing and improving students' social skills.